Frequency of Errors in Factors Affecting Complete Denture Satisfaction - A Tertiary Care Hospital Study - Rohma Umar Khan, Sheryar, Muhammad Hadeer Rabbani, Imsal Fatima, Tayyaba Hamid, Haziq Waseem, Sajid Naeem, Khezran Qamar, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To find out the frequency of errors made by dental undergraduate students in factors affecting denture satisfaction (retention, stability, support and esthetics) and find out the association of errors with patient age and gender. Study design: Cross sectional Observational study Place and duration: Prosthodontic Dept. of Lahore Medical & Dental College, Lahore, From March 8th 2024 till June 8th 2024. Methodology: A total of 124 dentures (62 maxillary dentures and 62 mandibular complete dentures) were included in the study. The dentures fabricated by BDS 3rd year and 4th year students; clinically assessed by senior doctors were selected. The patients were comfortably seated in the dental chair at the final insertion stage of the denture and the factors affecting denture satisfaction (retention, stability, support and esthetics) were clinically evaluated. Denture retention was assessed on 3 parameters; 1) over extended buccal or lingual flanges, 2) under extended buccal and lingual flanges, 3) inadequate post dam area. The denture stability was assessed on 3 parameters i.e.; 1) correct set up of teeth, 2) occlusal interferences, 3) correct flanges extension in sulci. Denture support was assessed on 3 parameters; 1) Adaptation to underlying tissue, 2) Adequate denture on favorable, 3) impression accuracy. 3 parameters for esthetics;1) polished surface finishing, 2) tooth shape and shade selection, 3) accurate arrangement of teeth. Results: The percentage of errors in all parameters of retention and denture support were less. The parameters determining denture stability i.e.; correct tooth setup and accurate flanges extension had a smaller number of errors, however percentage of errors of occlusal interference was found to be maximum;64.0%. The parameters determining denture esthetics i.e.; correct tooth selection shade/shape and accurate teeth arrangement had less errors however the polished surface finishing had the maximum number of errors;75.2%. The association of all the errors in parameters determining denture satisfaction with patient gender showed insignificant results; p<0.05; except parameter determining denture support (extension on favorable tissues) p<0.05. The correlation of age with all the parameters of factors determining patient satisfaction with dentures was insignificant, however the parameter of esthetics (tooth shape and shade selection) was found to have a significant correlation p<0.05. Conclusion: It can be concluded that the most frequently made errors in denture fabrication process by undergraduate students that affect patient satisfaction with the dentures were errors in parameters determining denture stability i.e.; occlusal interferences and denture esthetics i.e.; poor finishing and polishing of the polished surfaces. Keywords: Complete dentures, Denture retention, Denture esthetics, Denture stability, Errors, Gender, Undergraduates.